2019
DOI: 10.1097/pas.0000000000001348
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tumor Resembling Ovarian Sex Cord Tumor (UTROSCT)

Abstract: Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare mesenchymal neoplasm, of uncertain biological potential, that was recently reported to exhibit recurrent gene fusions involving NCOA2-3. The purpose of this study was to, using a larger sample size, better characterize the histopathologic and molecular diversity of UTROSCT. Twenty-six cases of UTROSCT from 5 institutions were selected for further study. Fluorescence in situ hybridization for NCOA1, NCOA2, NCOA3, ESR1 and GREB1, and targeted RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(131 citation statements)
references
References 39 publications
5
91
3
Order By: Relevance
“…6,8 The mean tumor size was 5.4 cm, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] which is quite similar to the 2 largest series (6.1 cm and 5.1 cm, respectively). As the largest cohort to date, the age of 7 GREB1::NCOA2 patients in our study was younger than 5 previously reported patients 7,8,11,13,40 (33 y-56 y, mean 48 y vs. 51 y-74 y, mean 60 y, P = 0.049). Five GREB1::NCOA1 patients were significantly younger than the 6 reported cases (50 y vs. 68 y, P = 0.001).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…6,8 The mean tumor size was 5.4 cm, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] which is quite similar to the 2 largest series (6.1 cm and 5.1 cm, respectively). As the largest cohort to date, the age of 7 GREB1::NCOA2 patients in our study was younger than 5 previously reported patients 7,8,11,13,40 (33 y-56 y, mean 48 y vs. 51 y-74 y, mean 60 y, P = 0.049). Five GREB1::NCOA1 patients were significantly younger than the 6 reported cases (50 y vs. 68 y, P = 0.001).…”
Section: Discussionmentioning
confidence: 77%
“…6 Recurrent NCOA1-3 rearrangements in UTROSCT have been described in recent reports, with GREB1 and ESR1 as the 2 most frequent partner genes. [7][8][9] GREB1:: NCOA1, GREB1::NCOA2, ESR1::NCOA2, and ESR1:: NCOA3 fusions have all been reported in UTROSCT. In addition, CTNNB1 fused with GREB1 was reported in 1 UTROSCT.…”
mentioning
confidence: 96%
“…[23][24][25] Alternatively, NCOA1 (nuclear receptor coactivator 1) and NCOA2 (nuclear receptor coactivator 2) genes are located on chromosomes 2p23.3 and 8q13.3, respectively, and encode for proteins that act as a coactivator for nuclear hormone receptors including steroid, thyroid, retinoid, and vitamin D. 26 In mesenchymal neoplasms, NCOA1/2 genes are involved in mesenchymal chondrosarcoma (HEY1::NCOA2), 27 a subset of biphenotypic sinonasal sarcoma (PAX3::NCOA1/ 2), 28,29 soft tissue angiofibroma (AHRR::NCOA2), 30 congenital/infantile spindle cell rhabdomyosarcoma (VGLL2::NCOA2, SRF::NCOA2, TEAD1::NCOA2), 31 and uterine tumor resembling ovarian sex cord tumor (ESR1::NCOA2/3, GREB1::NCOA1/2). 32 Nonetheless, the biologic relationship of the contributing gene partners in MEIS1::NCOA1/2 fusion genes is not well explored.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant treatment approaches for these eight patients with recurrence were different, and eventually, three patients died of this tumour. It has recently been found that UTROSCT has the recurrent fusion of NCOA2 or NCOA3, its partner genes are ESR1 and GREB1 14 and recurrence has been associated with GREB1, 5 which underscores the possible value of molecular detection in predicting prognosis. Therefore, for…”
Section: Discussionmentioning
confidence: 99%
“…FISH was performed as described previously. 5 Briefly, the unstained slides were deparaffinised, pretreated and hybridised to denatured probes. Then, after more than 6 hours of incubation at 37°C, the slides were washed and counterstained with diamidine phenyl indole (DAPI), mounted and analysed using a Zeiss fluorescence microscope (Olympus BX51, Tokyo, Japan).…”
Section: Fluorescence In Situ Hybridisation (Fish)mentioning
confidence: 99%